Medico-Legal Issues Dealing with inappropriate surgical behaviour - Rozovsky, Lorne; Rozovsky, Fay (Operating Room Nurses Association of Canada Journal, 1989)
Perhaps nothing was going the way the surgeon had planned it. Maybe he had fought with his spouse or a colleague. The bottom line was that the surgeon was in a foul mood, snapping at nursing staff in the operating room. At one point the surgeon became so outraged with the scrub nurse that instead of handing back an instrument to her, he ﬂung it over his shoulder. The scalpel narrowly missed striking a nurse entering the operating room. The nurse "told off’ the doctor and he stiﬂed his rage. That was the end of the episode. No reports were filed. No supervisors were informed of the occurrence. Although the facts may be slightly different, the scenario is sadly familiar to many operating room nurses. Should they grin and "bear it" or should they "fight back?" If they fight back, how should they proceed?